Tracing glass production in urban centers along the Silk Roads in the early Islamic period - Andrew Meek; St John Simpson; Nadine Schibille (iScience)
Summary: For most of the 1st millennium CE, glass was produced in a few industrial centers in the eastern Mediterranean and traded throughout the ancient world in the form of raw glass and finished objects. The chemical variability of glass is therefore limited, allowing economic and cultural exchange networks to be traced from production to consumer sites. This system of production and trade changed toward the end of the millennium. Using elemental analyses of glass from Merv (Turkmenistan), we reconstruct the transformation of the glass industry in the 9th century. Our data show that raw glass no longer traveled in large quantities over long distances, but that primary productions multiplied in urban centers along the medieval Silk Roads. We propose that the old model of a globalized glass trade disintegrates by the 9th century in favor of a more flexible and diverse production model, reflected in a variety of localized compositional groups.